Laughter Doeth Learning Good Like a Medicine - Celia Farr (Adult Education Research Conference, 2010)
Laughter and its significant benefits lower the affective filter in any learning environment. The release of laughter reduces perceived learning difficulties and lowers learning anxieties which are commonly found in the adult-learner classroom. With the introduction of appropriately-sensitive humor to the classroom, students forge a solid and personal foundation– upon which they can better build the scaffolding for present and future learning experiences. The role of humor and laughter in the adult-learner’s classroom not only enhances the overall learning experience, it also aids in retention of knowledge.